RELIGIOUS CHARACTER EDUCATION IN SHAPING STUDENTS' PERSONALITIES - Tri Wahyuni; Muhamad Slamet Yahya (Jurnal Konseling Pendidikan Islam, 2026)
Religious character education plays a crucial role in shaping students' personalities in an increasingly complex era of globalization. This study aims to explore how religious character education can be implemented in formal and non-formal education contexts and its impact on students' character development. The method used in this study is a literature review, which involves analyzing various sources, including books, journal articles, and educational policy documents. The results of the study indicate that religious character education not only focuses on teaching religious values but also encompasses the development of morality, ethics, empathy, and tolerance. In addition, religious character education also prepares students to face challenges in the era of globalization and digitalization. Thus, religious character education serves as a foundation that guides behavior, strengthens identity, and shapes students' moral resilience, so that they can contribute positively to life in a diverse society.